ANALISIS AWAL SELF-CONFIDENCE DAN METACOGNITIVE AWARNESS MAHASISWA CALON GURU BIOLOGI - Muh.Amin, Astuti; Karmila, Fitriyah; Febrianti, Dian Trisma; M Soleman, Rahmatia (Jurnal Biogenerasi, 2024)
Self-confidence is very important, because success in the learning process can be influenced by self-confidence. Meanwhile, metacognitive awareness needs to be developed because it is an important key in achieving meaningful goals and longer retention of material understanding. This study aims to (1) identify and analyze the self-confidence of prospective biology teacher students in Ternate City, North Maluku; (2) Identify and analyze the metacognitive awareness of prospective biology teacher students in Ternate City, North Maluku. This study is a quantitative study with a descriptive method. The research instrument is a non-test instrument, namely a self-confidence questionnaire and a metacognitive awareness questionnaire that have been validated. The level of self-confidence of prospective biology teacher students is 20.00% in the high category; 13.33% is in the moderate category and 66.67% is in the low category. While the level of metacognitive awareness of prospective biology teacher students is 23.33% in the less category; 43.34% is in the sufficient category and 33.33% is in the good category. The conclusion of the study is that the self-confidence and metacognitive awareness scores of prospective biology teachers are still low.